IMPLEMENTATION OF SUFISTIC EDUCATION VALUES OF QADIRIYYAH WA NAQSYABANDIYYAH TARIQA - Kafaa Ainul Aziz (Universitas Islam Malang, 2023)
By sunnatullah every creature experiences a period of birth, development, maturity, aging and then death, including humans. Old age or old age is actually a natural process, but specifically for humans, this period leaves many problems both for those concerned and those around them, especially the problem of difficulties in adjustment and self-control. Based on the hadith of the Prophet saw. that every disease has a cure, except for old age, so old age, including diseases, needs to find a solution, primarily a solution so that the elderly (elderly humans) can have self-control to adjust to the life they live. However, often because of various impulses and other disturbances, how difficult it is to regulate self-control. To achieve complete mental health in humans, education for something must be carried out consistently and within a certain frequency to play a role as a means of self-control, as is often found in Sufistic education in the Qodiriyah wa Naqsabandiyah Order at the Miftahul Huda Islamic Boarding School, Gading, Malang.